Desarrollo psicomotor y su relación con la alimentación en los niños de los CNH de Tenería - Carigán y Consacola MIES-Loja - Cuenca Morocho, Gabriela Belén (2015)
This research aims to determine the feeding practices of infant and young child and its influence on the psychomotor development. It is transverse, correlational study, carried out in 103 children from 0 to 36 months enrolled in the program “Growing with our Children” (GOC) in Tenería - Carigán and Consacola of the Ministry of economic Inclusion and Social MIES-LOJA in 2014, for the collection of information, surveys were conducted to mothers or caregivers and psychomotor development was assessed using the Denver test. From all children who had an early start breastfeeding the 68.75% obtained a normal Denver test, unlike those who did not receive an early initiation of breastfeeding, in which the 65, 22% obtained doubtful test and 13.04% abnormal. From children receiving exclusive breastfeeding the 63.24% were normal and only 2.94% obtained an abnormal test, unlike those who did not receive exclusive breastfeeding 8.57% of the tests were abnormal. Of the children who received the minimum dietary diversity, 55% obtained a normal test, and only 5% abnormal; and those who did not receive minimum dietary diversity 66.67% the test was abnormal. It is concluded that appropriate feeding practices positively affect the psychomotor development. It is need that institutions working for the welfare of children as it is the Ministry of Economic and Social Inclusion through GOC, the encouragement in the initiation and maintenance of appropriate feeding practices that ensure the integral development of children in Loja province. Keywords: feeding practices, psychomotor development, children